The Neurophysiological and Psychological Mechanisms of Qigong as a Treatment for Depression: A Systematic Review and Meta-Analysis - So, Wendy Wing Yan; Cai, Shuhe; Yau, Suk Yu; Tsang, Hector Wing Hong (Frontiers in Psychiatry, 2019)
Objective: An increasing number of studies have shown the anti-depressive effect of qigong However, the underlying mechanism of it remains poorly understood. This study aims to systematically review and meta-analyze existing literature on the mechanism of qigong in reducing depression. Method: The review process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Randomized controlled trials of qigong were searched from Psyinfo, Pubmed, Embase, Science Direct, and Academic Search Premier from inception to Dec 2018. Studies which involved depression and any neurophysiological or psychological mechanisms as outcomes were included. Publication bias was tested before conducting meta-analysis. Two independent raters were involved for the entire review process. Results: A total of nine studies were identified which covered both neurophysiological and psychological mechanisms. Among these selected studies, seven were involved in meta-analysis, which suggested that qigong was effective in alleviating depression (SMD = -0.27, p < 0.05, I 2 = 27%). A significant effect was also found for diastolic blood pressure (SMD = -1.64, p < 0.05, I 2= 31%). However, no significant effect was found for cortisol level and systolic blood pressure. Conclusions: This review shows that qigong is effective in reducing depression through activating the parasympathetic nervous system. Future studies with higher quality of research methodology with less selection and attrition bias should be conducted to unravel the possible anti-depressive effect of qigong.